2019
DOI: 10.1021/acsami.8b19240
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic Ternary Organic Solar Cells with Porphyrin Dimers and Absorption-Complementary Benzodithiophene-based Small Molecules

Abstract: Diketopyrrolopyrrole–ethynylene-bridged porphyrin dimers are capped with electron-deficient 3-ethylrhodanine (A2) via a π-bridge of phenylene ethynylene, affording two new acceptor–donor–acceptor structural porphyrin dimers (DPP-2TTP and DPP-2TP) with strong absorption in ranges of 400–550 nm (Soret bands) and 700–900 nm (Q bands). Their intrinsic absorption deficiency between the Soret and Q bands could be perfectly compensated by a wide-bandgap small molecule DR3TBDTTF (D*) with absorption at 500–700 nm. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…Compared with polymer-based OSC, NFSM-OSC is more suitable as a research model device, which can more easily establish clear relationships between the structure and performance [4][5][6][7][8]. However, the power conversion efficiencies (PCEs) of current state-of-the-art NFSM-OSCs are still much lower than that of polymer-based OSCs because small molecules cannot form pre-aggregation in solution like most high-performance polymers [9-11], and have similar acceptor-donor-acceptor (A-D-A) skeleton structures with high efficiency non-fullerene acceptors, making it difficult to regulate their morphology [12][13][14][15][16][17][18][19][20][21]. To date, though considerable efforts have been made in the research of NF acceptors and a number of high-performing materials have been reported, the study on small molecule donors for efficient NFSM-OSCs is relatively lagging [1, [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with polymer-based OSC, NFSM-OSC is more suitable as a research model device, which can more easily establish clear relationships between the structure and performance [4][5][6][7][8]. However, the power conversion efficiencies (PCEs) of current state-of-the-art NFSM-OSCs are still much lower than that of polymer-based OSCs because small molecules cannot form pre-aggregation in solution like most high-performance polymers [9-11], and have similar acceptor-donor-acceptor (A-D-A) skeleton structures with high efficiency non-fullerene acceptors, making it difficult to regulate their morphology [12][13][14][15][16][17][18][19][20][21]. To date, though considerable efforts have been made in the research of NF acceptors and a number of high-performing materials have been reported, the study on small molecule donors for efficient NFSM-OSCs is relatively lagging [1, [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Over the past several years, we and other groups have steadily worked for the development of porphyrin SM electron donors in OSCs due to their excellent super p-conjugation properties, tremendous light-harvesting capabilities, exceptional charge transport mobilities, and easy processability with fullerene acceptors, as a result, achieving high PCEs up to 10%. [42][43][44][45][46][47][48][49][50][51][52][53][54][55] One major disadvantage of porphyrin derivatives for OSCs is that they usually show a deep valley between the intense Soret band (400-500 nm) and Q-bands (650-800 nm). 45,56 It is still challenging to design a porphyrin molecule with a full spectrum from 300 nm to 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50][51][52][53][54][55] One major disadvantage of porphyrin derivatives for OSCs is that they usually show a deep valley between the intense Soret band (400-500 nm) and Q-bands (650-800 nm). 45,56 It is still challenging to design a porphyrin molecule with a full spectrum from 300 nm to 900 nm. Recently, ternary OSCs were proposed to be used as the third component as an absorption complementary donor or acceptor to achieve a full absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] And the expanded and enhanced absorptions in J-aggregation-based films provide the potential chance to fabricate broader light response and larger short-circuit current (J SC ) solar cell devices. Some of porphyrin derivatives are near-infrared (NIR) organic semiconductors with optical bandgap less than 1.5 eV which have attracted much attention due to their great contribution to the field of NIR photodetector, 29,30 SM-OSCs, [31][32][33][34][35][36][37][38][39][40][41] ternary solar cells [42][43][44][45][46] and tandem solar cells. 47,48 In this contribution, we report dimer porphyrin molecule ZnP2-DPP 49 (Figure 1 .…”
Section: Introductionmentioning
confidence: 99%